Evaluation of The Policy of Electronic Issuance of SPPT PBB-P2 at UPPPD Penjaringan North Jakarta in 2021 - 2023 - Purwosusanto, Lilik; Salomo, Roy Valiant (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2024)
This research aims to analyze and describe the evaluation of the PBB-P2 electronic SPPT issuance policy at UPPPD Penjaringan, North Jakarta. The research approach uses a qualitative approach with a descriptive type using secondary data from literature studies and document studies related to the main problem. The theory used is policy evaluation expressed by Dunn (2003). The background to this research is that due to the increasing number of taxpayers who download SPPT PPB-P2, there are still arrears in PBB-P2 payments, indicating that there are weaknesses in digitalization-based administration. The results of the policy evaluation show that the output achieved is less effective based on the amount of SPPT that must be paid and there are still arrears. The e-SPPT PBB-P2 publishing policy is quite efficient in increasing the number of taxpayers who download SPPT PBB-P2 electronically. However, tax officers are less responsive in increasing taxpayer knowledge so efforts are still needed to carry out outreach. The policy of issuing e-SPPT PBB-P2 is considered appropriate as an effort to increase PBB-P2 revenue from regional taxes in DKI Jakarta Province.